Damage of 3D tungsten targets in the course of ITER ELM-like heat loads - Herashchenko, S.S.; Makhlaj, V.A.; Aksenov, N.N.; Byrka, O.V.; Chebotarev, V.V.; Kulik, N.V.; Lebedev, S.I.; Shevchuk, P.B.; Staltsov, V.V. (Вопросы атомной науки и техники, 2017)
The damage of tungsten target under repetitive plasma loads have been studied with a quasi-stationary plasma accelerator QSPA Kh-50. The target construction was close to the ITER divertor reference design. The plasma stream parameters were relevant to ITER ELMs (surface heat load of 0.9 MJ/m² and pulse duration of 0.25 ms). The features of surface erosion and particle emission have been investigated in the course of increasing number of plasma pulses. The number of solid/droplet particles separated from the exposed target and their dynamics depend on the applied exposition dose. The contribution of different erosion mechanisms to the tungsten target destruction was evaluated. Изучены повреждения вольфрамовой мишени при многократном облучении плазмой в квазистационарном плазменном ускорителе КСПУ Х-50. Мишень имела конструкцию, близкую к строению компонентов дивертора ИТЭР. Параметры потоков плазмы выбраны близкими к ELM в ИТЭР (тепловая нагрузка на поверхность составляла 0,9 МДж/м², длительность импульса – 0,25 мс). Исследованы особенности эрозии поверхности и эжекции капель при увеличении количества плазменных импульсов. Показано, что количество пыли/капель и динамика частиц, отделившихся от облучаемой мишени, зависят от дозы облучения. Анализируется вклад разных механизмов эрозии в разрушение вольфрамовой мишени. Вивчено пошкодження вольфрамової мішені під час багаторазового опромінення плазмою в квазістаціонарному плазмовому прискорювачі КСПП Х-50. Мішень мала конструкцію близьку до будови компонентів дивертора ІТЕР. Параметри потоків плазми обрані близькими до ELM в ІТЕР (теплове навантаження на поверхню становило 0,9 МДж/м², тривалість імпульсу – 0,25 мс). Досліджено особливості ерозії поверхні та ежекції крапель зі збільшенням кількості плазмових імпульсів. Показано, що число та динаміка пилу/крапель, які відокремилися від опромінюваної мішені, залежать від дози опромінення. Визначено внесок різних механізмів ерозії в руйнування вольфрамової мішені.